UJI EFEKTIVITAS ANTIMIKROBA PADA EKSTRAK DAUN GAMBIR (UNCARIA GAMBIER ROXB.) DAN DAUN SIRIH HIJAU (PIPER BETLE LINN.) TERHADAP STREPTOCOCCUS MUTANS, ESCHERICHIA COLI DAN CANDIDA ALBICANS - Reki Wicaksono Ashadi (Universitas Djuanda, 2015)
Gambier contains two main components, namelycatechin and katekutanat acid. According to Lemmens (1999), gambier have three benefits: fortanning leather; as a stimulant as well as medicine. This study aims to determine the concentrationof the inhibition gambier (Uncaria gambier Roxb.) and betelleaf (Piper betle Linn.) as well astocompare the differences in the inhibition of growth of Streptococcusmutans, Escherichiacoli and Yeast Candida albicans. The Results showed that gambier extract (Uncaria gambier Roxb.) and green betelleaf (Piper betle Linn.) indicates that the leaf extract of betelleaf and gambier have no activity on hibiting the growth of Candida albicans. However extract from betelleaf can inhibit the growth of Streptococcus mutans and Escherichia coli with a minimum concentration levels of 25%.